Patient satisfaction with the first contact physiotherapy service: Results from the national evaluation survey. (28th October 2021) - Wood, Lianne; Bishop, Annette; Goodwin, Rob; Stynes, Siobhan
Abstract: Background: Musculoskeletal (MSK) First Contact Physiotherapists (FCPs) are diagnostic clinicians able to assess and manage undifferentiated and undiagnosed MSK presentations. The FCP role in primary care has been introduced to allow patients with MSK pain to see a FCP directly rather than wait to see a General Practitioner (GP) first, which improves capacity within primary care. A national evaluation was undertaken of the FCP model. This article reports the thematic analysis of the free‐text responses of patients who participated in the national evaluation. Methods: An online platform collected patient‐reported experience and outcomes following the FCP consultation and at 1, 2 and 3 months follow‐up. Free‐text responses to the Friends and Family test, reasons for consulting another health care professional (HCP) and general comments were thematically analysed and grouped according to their responses. Results: Over 13 months, 680 of 2825 registered patients (24%) completed the initial questionnaire and 54% ( n  = 370) completed the 3‐month follow‐up. During the course of the evaluation, 785 participants provided free‐text responses. Themes identified from free‐text responses were: communication and knowledge, clinicians' characteristics, efficiency, treatment provided, assessment skills and service provided in comparison to GP care. Complaints represented 4% ( n  = 26 comments) of total feedback. The main reasons for consulting other HCPs after seeing a FCP were persistent pain, delays in referrals or already attending NHS physiotherapy. Conclusion: Thematic analysis of free‐text responses in the national FCP evaluation provides context and detail to the positive outcomes reported by patients after consulting a FCP in primary care.